Trans(vivências): entre os direitos humanos e a realidade social - Vieira, Fernanda de Sousa; Amorim, Sylvia Maria Godoy [UNESP]; Brancaleoni, Ana Paula Leivar [UNESP]; Oliveira, Rosemary Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
People who identify themselves as transgender experience discrimination and social exclusion in a marked manner. Therefore, the importance of the formation of arenas in which their demands, struggles and their interpretation of their rights and state in society can be heard, is emphasized. This study together with a group of transvestites aimed to reframe the rights and maintain the mental and physical health of this group on people who are also part of the population and deserve to have their citizenship recognized.

Pessoas de identidade trans vivenciam a discriminação e exclusão social de forma acentuada. Assim, destaca-se a importância da constituição de espaços em que possam ser ouvidas em suas demandas, vivências e compreensões acerca de seus direitos e condição na sociedade. Neste estudo, objetivou-se construir, junto a um grupo de travestis, a ressignificação sobre direitos e a manutenção da saúde mental e física dessas pessoas, que também fazem parte da população e merecem ter sua cidadania reconhecida.
Keywords: Identity; Transvestites; Human rights; Identidade; Travestis; Direitos humanos